Modeling and Control of a Novel Permanent Magnet Linear Motor - Hasırcı, Uğur; Demirkol, Ziya (Duzce Universitesi Bilim ve Teknoloji Dergisi, 2025)
This paper concerns on modeling and linear controller design of a novel permanent magnet DC linear motor. The paper first introduces the novelty of designed and implemented motor, and then presents its dynamical model. By using the developed model, a linear controller has been designed and the results of the numerical simulation of the designed controller have been presented to show the effectiveness and stability of the designed controller. Some future prospects for the designed and simulated controller have also been provided.
Keywords: Technology; Science (General); T; Science; Q; permanent magnet dc linear motors; simulation; Engineering (General). Civil engineering (General); simülasyon; controller design; Q1-390; kalıcı mıknatıslı dc lineer motorlar; kontrolör tasarımı; TA1-2040